Imagery Interventions and Cognitive‐Behavioural Therapy for Psychological Complaints Related to Bullying: A Systematic Review and Meta‐Analysis - Meng Liang; Gerly Tamm; Olivia De Laere; Yannick Vander Zwalmen; Ernst H. W. Koster (Clinical Psychology & Psychotherapy, 2026)
ABSTRACT Bullying is associated with internalizing symptoms and impaired everyday functioning. Cognitive‐behavioural therapy (CBT) and imagery interventions have been studied as treatments to improve mental health after such experiences. This meta‐analysis aimed to evaluate the effects of individual CBT and imagery interventions in targeting internalizing symptoms (negative affect, depression, anxiety and post‐traumatic stress symptoms) and improving self‐perception and coping in bullying victims. Systematic searches of PubMed, PsycInfo, Embase and Web of Science identified 23 studies applying CBT ( n = 15) and imagery interventions ( n = 8) in bullying victims. Risk of bias and random‐effects meta‐analyses were conducted for pre ‐ post and pre ‐ follow‐up comparisons. Sensitivity analyses and meta‐regressions explored potential moderators. Unadjusted analyses showed reductions in internalizing symptoms pre‐ to post ‐ intervention ( k = 21, g = 0.72). These symptoms were maintained at follow‐up assessments ( k = 9, g = 0.54). Similar initial improvements emerged for self‐perception and coping outcomes ( k = 15, g = 0.75). However, substantial heterogeneity existed ( I 2 = 68%–98%). Crucially, after adjusting for publication bias, the pre–post internalizing effect dropped to g = 0.26 and was no longer statistically significant. Conversely, the adjusted effect for self‐perception and coping increased to g = 0.98, whereas the follow‐up internalizing effect decreased ( g = 0.37) but remained significant. Both CBT and imagery interventions may offer potential benefits for bullying victims in reducing internalizing symptoms and in improving self‐perception and coping abilities. However, large heterogeneity, methodological limitations and publication bias warrant cautious interpretation. Further high‐quality controlled trials are needed to establish the robustness and clinical efficacy of these interventions.